Improving Obstetric Hemorrhage Morbidity and Mortality by a Checklist-based Management Protocol [26R]. (May 2018) - Smith, Rachael; Foley, Michael; Hermann, Catherine; Erickson, Laurie; Mercer, Laura
Abstract : INTRODUCTION: Postpartum hemorrhage (PPH) is a leading cause of maternal morbidity and mortality in the US. Many obstetrical teams rely on clinical judgment when managing PPH, however critical care research has demonstrated that specific and uniform protocols result in better outcomes. This study analyzed the effect of implementation of a checklist-based management protocol for PPH. METHODS: A checklist was developed by a multidisciplinary team for the management of PPH that focused on timely diagnosis and systematic administration of uterotonics, invasive interventions, transfusions, and lab draws. A training video was used to introduce the protocol to nursing and physician staff. Following formal implementation, pre and post-protocol analyses were performed using nine matched months from 2015 and 2016. Outcome measures were surrogates for maternal morbidity. RESULTS: 147 subjects met criteria in the pre-protocol group and 150 met criteria in the post-protocol group. Within the analysis of the first three matched months, there was a significant decrease in surgical interventions for PPH (p value 0.039) and a decreased length of stay for PPH following cesarean sections (p value 0.039). In the 9 month analysis, there was a significant decrease in severe PPH as defined by an EBL of >2L (p value 0.035). CONCLUSION: The implementation of a checklist based management protocol for PPH has shown a promising trend in improving maternal outcomes and healthcare delivery for obstetric hemorrhage. Specifically, significant improvement in severe PPH rates was demonstrated. Further multi-center research is needed to demonstrate consistent beneficial effects of such protocols.